2002
DOI: 10.1105/tpc.005207
|View full text |Cite|
|
Sign up to set email alerts
|

Rose Scent

Abstract: For centuries, rose has been the most important crop in the floriculture industry; its economic importance also lies in the use of its petals as a source of natural fragrances. Here, we used genomics approaches to identify novel scentrelated genes, using rose flowers from tetraploid scented and nonscented cultivars. An annotated petal EST database of ‫ف‬ 2100 unique genes from both cultivars was created, and DNA chips were prepared and used for expression analyses of selected clones. Detailed chemical analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
114
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 267 publications
(118 citation statements)
references
References 39 publications
2
114
0
2
Order By: Relevance
“…However, we have shown that ODO1 is a MYB that exerts influence over multiple genes involved in generating precursors for volatile benzenoid biosynthesis ( Figure 5A). Two MYBs have been identified in fragrant red roses (Guterman et al, 2002), which also produce volatile benzenoids. However, these MYBs have the highest similarity with GhMYB9 and PsMYB26, which are phylogenetically unrelated to ODO1 and which are likely to regulate phenylpropanoid genes involved in flavonoid synthesis (Figure 2).…”
Section: Odo1 Is Distinct From Other Floral Myb Proteinsmentioning
confidence: 99%
“…However, we have shown that ODO1 is a MYB that exerts influence over multiple genes involved in generating precursors for volatile benzenoid biosynthesis ( Figure 5A). Two MYBs have been identified in fragrant red roses (Guterman et al, 2002), which also produce volatile benzenoids. However, these MYBs have the highest similarity with GhMYB9 and PsMYB26, which are phylogenetically unrelated to ODO1 and which are likely to regulate phenylpropanoid genes involved in flavonoid synthesis (Figure 2).…”
Section: Odo1 Is Distinct From Other Floral Myb Proteinsmentioning
confidence: 99%
“…cDNA was labeled indirectly with succinimidyl ester Cy3/ Cy5 as described previously (Guterman et al, 2002). For each one of the two biological repetitions, two hybridizations with swapped dye labeling reactions were performed (see Guterman et al, 2002). Separate images for each fluorescent probe were acquired using ScanArray 4000 software (Packard BioScience) at a resolution of 10 mm per pixel, adjusting the photomultiplier and laser power to achieve an optimal distribution of signals without minimal saturation.…”
Section: -Mer Oligonucleotide Arraysmentioning
confidence: 99%
“…One hundred micrograms of total RNA was subjected to reverse transcription reaction using dNTPs mix containing 5-3 aminoallyl dUTP. cDNA was labeled indirectly with succinimidyl ester Cy3/ Cy5 as described previously (Guterman et al, 2002). For each one of the two biological repetitions, two hybridizations with swapped dye labeling reactions were performed (see Guterman et al, 2002).…”
Section: -Mer Oligonucleotide Arraysmentioning
confidence: 99%
“…Plants were transferred to S-sufficient or S-deprived medium and grown for up to 1 week (168 h). Rosette leaves and roots were harvested at 3,6,12,24, 48, and 168 h after transfer, immediately frozen with liquid nitrogen, and stored at Ϫ80°C until use.Metabolome Analyses-Fourier-transform ion cyclotron resonance mass spectrometry analysis was used to conduct non-targeted metabolomic profiling (6). Targeted metabolic profiling of amino acids, Oacetyl-L-serine (OAS), anions, organic acids, and sugars was performed by high performance liquid chromatography and capillary electrophoresis as described (9).…”
mentioning
confidence: 99%